2017
DOI: 10.1002/solr.201700159
|View full text |Cite
|
Sign up to set email alerts
|

Possible Candidates for Impurities in mc‐Si Wafers Responsible for Light‐Induced Lifetime Degradation and Regeneration

Abstract: We examine the light-induced carrier lifetime degradation and regeneration at elevated temperature in multicrystalline silicon (mc-Si) wafers of different thicknesses. The experimental results show that the thinner the wafer the less pronounced the degradation is and the faster the regeneration takes place. We interpret this result in the framework of a recently proposed defect model, where the lifetime regeneration is attributed to the diffusion of the recombination-active impurity to the wafer surfaces, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 30 publications
(43 reference statements)
2
37
0
Order By: Relevance
“…Thus, the reduced LeTID could be at least partly explained by a heavier phosphorus emitter, and hence enhanced gettering, in the b-Si cells, 6 although the defect responsible for the degradation is likely another impurity than Fe. 40,41 This explanation supports the conclusion that LeTID is a bulk effect, as suggested previously, 12,23,24 instead of, eg, deterioration of rear surface passivation.…”
Section: Physical Background For Impact Of B-si On Letidsupporting
confidence: 89%
See 1 more Smart Citation
“…Thus, the reduced LeTID could be at least partly explained by a heavier phosphorus emitter, and hence enhanced gettering, in the b-Si cells, 6 although the defect responsible for the degradation is likely another impurity than Fe. 40,41 This explanation supports the conclusion that LeTID is a bulk effect, as suggested previously, 12,23,24 instead of, eg, deterioration of rear surface passivation.…”
Section: Physical Background For Impact Of B-si On Letidsupporting
confidence: 89%
“…The acidic‐textured cells are slightly thicker, ~165 μm, while the non‐textured edges of the b‐Si cells, which experienced SDR instead of acidic‐texturing, have a final thickness between these two (~155 μm). Interestingly, Bredemeier et al reported that wafer thinning reduces LeTID‐causing effective defect density . In our experiments, the non‐textured edges of the SiN x ‐passivated b‐Si cells show more pronounced degradation in the PL map (Figure C) than the thicker acidic‐textured cells (Figure F).…”
Section: Resultsmentioning
confidence: 91%
“…In the following regeneration process, these metal atoms are assumed to diffuse to the surface where they become electrically inactive. In a recent work, the same authors have presented LeTID degradation and regeneration results for lifetime wafers with different thicknesses . It was found that the regeneration process becomes the faster the thinner the cells are, which can be explained by the assumed diffusion process of the unknown metal species to the surface.…”
Section: Performance Parameters Of the Investigated Cellsmentioning
confidence: 99%
“…Whether or not Ni is directly involved in the LeTID degradation/regeneration process in a mechanism discussed in refs. still has to be checked. It could also be possible that, if according to the Bredemeier model the Ni complex decays during degradation and Ni atoms diffuse during regeneration, some of the released Ni atoms precipitate out as NiSi 2 instead of diffusing to the surface.…”
Section: Performance Parameters Of the Investigated Cellsmentioning
confidence: 99%
“…They reduce the carrier lifetime of silicon materials in both the dissolved state and the precipitated state, and are thus detrimental to silicon solar cells . Knowledge of the metal concentrations in silicon materials is also significant for the studies of other defects, including light and elevated temperature‐induced degradation, decorated crystal defects such as dislocations and grain boundaries, copper‐related light‐induced degradation, boron‐oxygen‐related defects, ring defects, and so on. The metal concentrations in multicrystalline silicon (mc‐Si) ingots have been successfully determined by applying neutron activation analysis in previous studies .…”
mentioning
confidence: 99%